Micah's Teraphim - Cox, Benjamin D. (The journal of Hebrew scriptures, 2012)
In publications in the 1990’s, K. van der Toorn and T.J. Lewis revived and argued persuasively for a reconstruction identifying the biblical תרפים as representations of a family’s deceased ancestors. In this paper, we look at the story of Micah’s תרפים in Judges 17-18 to suggest that this identification of the תרפים as ancestor figurines is well supported by and, indeed, clarifies certain details of the Micah account. Our interpretation also illuminates other תרפים accounts, for example, Rachel’s theft of her father Laban’s תרפים in Gen 31:19-35.